أثر برنامج تربوي في تنمية التضامن الاجتماعي لدى طلاب المرحلة الإعدادية - الحسين، أحمد إياد سالم; الطريا، أحمد وعد الله حمد الله (جامعة الموصل - كلية الآداب, 2021)
يهدف البحث إلى التعرف على أثر برنامج تربوي في تنمية التضامن الاجتماعي لدى طلاب المرحلة الإعدادية، تكونت عينة البحث من (43) طالبا من طلاب الصف الرابع العلمي وتم توزيعهم بشكل عشوائي إلى مجموعتين بواقع (23) طالبا للمجموعة التجريبية وبواقع (20) طالبا للمجموعة الضابطة، إذ تلقى إفراد المجموعة التجريبية التدريب على البرنامج التربوي الذي تكون من (13) درسا أما الضابطة لم يتلق إفرادها أي تدريب، ولتحقيق هدف البحث واختبار فرضياته، قام الباحثان ببناء برنامج التضامن الاجتماعي الذي تكون بصيغته النهائية من (13) درسا واتسم بالصدق والثبات، وبعد تنفيذ البرنامج وتطبيق المقياس قبليا وبعديا على أفراد عينة البحث وتحليل البيانات إحصائيا باستعمال الوسائل الإحصائية (الاختبار التائي لعينتين مستقلتين، اختبار مربع كاي، معامل الارتباط بيرسون، معادلة حجم الأثر)، وأظهرت النتائج ما يأتي: 1- وجود فروق ذات دلالة إحصائية عند مستوى دلالة (0,05) بين متوسطي درجات التضامن الاجتماعي في الاختبار البعدي لدى أفراد المجموعتين التجريبية والضابطة ولصالح المجموعة التجريبية بسبب تطبيق البرنامج التربوي على المجموعة التجريبية. 2- وجود فروق ذات دلالة إحصائية عند مستوى دلالة (0,05) بين متوسطي درجات (تنمية) التضامن الاجتماعي لدى أفراد المجموعتين التجريبية والضابطة لصالح المجموعة التجريبية بسبب ارتفاع معدل الفرق. 3- وجود فروق ذات دلالة إحصائية عند مستوى دلالة (0,05) بين متوسطي درجات التطبيقين القبلي والبعدي في مقياس التضامن الاجتماعي لدى أفراد المجموعة التجريبية ولصالح درجات البعدي. The aim of the research is to identify the impact of an educational program on developing social solidarity among middle school students. The research sample consisted of (43) students of the fourth grade of scientific branch and they were randomly distributed into two groups of (23) students for the experimental group and (20) students for the control group. The members of the experimental group received training on the educational program which consisted of (13) lessons; while the control group did not receive any training, In order to achieve the goal of the research and test its hypotheses, the two researchers built a social solidarity program, which was finalized in (13) lessons and was characterized by honesty and stability. After implementing the program and applying the scale before and after the individuals of the research sample and analyzing the data statistically using statistical means (T-test for two independent samples, a square test. Kay, Pearson Correlation Coefficient, Impact Size Equation), and the results showed the following: - The presence of statistically significant differences at the level of significance (0‚05) between the mean scores of social solidarity in the post test for members of the experimental and control groups and in favor of the experimental group due to the application of the educational program to the experimental group. - The presence of statistically significant differences at the level of (0,05) between the average degrees of (development) social solidarity among members of the experimental and control groups in favor of the experimental group due to the high rate of difference. - The presence of statistically significant differences at the level of significance (05‚0) between the mean scores of the pre and post applications in the social solidarity scale among the members of the experimental group and in favor of the scores of the post.
Keywords: البرامج التربوية -- التضامن الاجتماعي -- طلبة المرحلة الإعدادية -- العراق